The Effect of Expected Years of Schooling and Adjusted Expenditure per Capita on Life Expectancy in East Kalimantan Province (2022- 2024) - Muhammad Dzaki Rifa'i; Santoso Parlindungan Togatorop; Muhammad Ilma Yusrian Fahmi; Inayah Ramadhani; Andi Nurfadillah Hasan; Rajiansyah Rajiansyah; Fahrul Agus (Buletin Ekonomika Pembangunan, 2026)
This study examines the impact of Expected Years of Schooling (EYS) and Adjusted Expenditure per Capita (AEPC) on Life Expectancy (LE) in 10 regencies and cities in East Kalimantan Province during 2022–2024 (BPS East Kalimantan Province, 2024). This topic is relevant because East Kalimantan exhibits strong economic performance yet continues to face disparities in human development across regions. At the same time, empirical studies that directly link education and household purchasing power to life expectancy at the district and municipal level in this province remain limited (Susanti Hidayat, 2020; Williyan Hasmarini, 2024). The novelty of this study lies in the use of recent panel data for 10 regencies and cities that simultaneously incorporate AEPC and EYS as determinants of LE, thereby providing more context-specific empirical evidence for East Kalimantan (Hasanah et al., 2021; Swastika Arifin, 2023). The study employs secondary data sourced from BPS East Kalimantan Province, comprising EYS, AEPC, and LE for 2022–2024, which are analysed using panel data regression, specifically the Common Effect Model (CEM). The model's validity is assessed using statistical tests, namely the t-test, the F-test, and the coefficient of determination (Statistics Indonesia, 2024; BPS East Kalimantan Province, 2024). The estimation results indicate a positive and statistically significant relationship between EYS and AEPC, and an increase in LE, while these two variables jointly explain approximately 71–73% of the variation in LE across regencies and cities (Hasanah et al., 2021; Meilinna et al., 2024). These findings suggest that expanding access to and improving the quality of education, alongside strengthening household economic capacity, are crucial prerequisites for improving health status and overall quality of life in East Kalimantan (Sari Syechalad, 2022; Swastika Arifin, 2023). Keywords: Life Expectancy (LE), Expected Years of Schooling (EYS), Adjusted                   Expenditure per Capita (AEPC), Panel data, Multiple linear regression.